INTEGRATING LOCAL CULTURAL PRACTICES INTO SOCIAL STUDIES LEARNING: AN ETHNOGRAPHIC STUDY OF KANKAIN KARKARA AND CULTURAL AWARENESS AMONG ELEMENTARY STUDENTS IN PAPUA - Yan Dirk Wabiser; Alim Mutaqin; Mamberuman Inggamer; Marthen; Fitriani (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2025)
This study examines the role of Kankain Karkara in fostering cultural awareness and enhancing the quality of Social Studies (IPS) education for fifth-grade students at SDN II Abepura. Additionally, it explores the methods of integrating Kankain Karkara into the curriculum and identifies both supporting and inhibiting factors. Employing a qualitative approach with an ethnographic design, the study involved participants including the Social Studies teacher, fifth-grade students, the school principal, and local customary leaders. Data were gathered through participant observation, in-depth interviews, and documentation, and analyzed using an interactive model of data reduction, display, and conclusion drawing. Triangulation and member checking were applied to ensure data trustworthiness. The findings reveal that Kankain Karkara is utilized as both a thematic discussion and a deliberative learning model, enriching Social Studies lessons with character-building values. This integration not only strengthens students' knowledge and pride in local culture but also fosters respect for customary norms, increasing motivation and participation in Social Studies. Key factors supporting its implementation include teacher commitment, cultural alignment of students, and support from customary leaders. However, challenges such as limited instructional time, lack of written guidelines, and diverse student backgrounds hinder its full potential.